Ultrasound Fragility Score: An innovative approach for the assessment of bone fragility. (April 2017) - Greco, Antonio; Pisani, Paola; Conversano, Francesco; Soloperto, Giulia; Renna, Maria Daniela; Muratore, Maurizio; Casciaro, Sergio
Highlights: A new ultrasound approach for bone fragility assessment was introduced. The new parameter (Fragility Score) showed good correlations with FRAX® predictions. Fragility Score could become a new method for fracture risk prediction in clinics. Abstract: Aim of this paper was to assess the clinical effectiveness of a novel ultrasound (US) approach for the estimation of bone fragility. A total of 85 female patients (40–80 years) were recruited and underwent conventional DXA investigations of both lumbar spine and proximal femur, an abdominal US scan of the lumbar spine and the FRAX® questionnaire for the calculation of osteoporotic fracture probabilities. Acquired US data were analyzed through an automatic algorithm that calculated the Fragility Score (F.S.), a parameter that estimates skeletal fragility from dedicated spectral and statistical analyses. F.S. showed a good correlation with the most reliable fracture risk predictions obtained by FRAX® ( r  = 0.71, p  < 0.001). Since this correlation level with FRAX® outcomes was much better than lumbar BMD one (| r | = 0.43) and very similar to that obtained for femoral neck BMD (| r | = 0.72), F.S. has the potential to become a simple and non-ionizing method for bone fragility assessment.